Diversidad y abundancia de abejas silvestres en dos ambientes del espinal entrerriano - Annoni, Giovana Mariela; Casse, Maria Florencia; Roman, Lilian Mabel; Cavigliasso, Pablo (Sociedad Entomológica Argentina, 2025)
Poster y resumen